Association of periodontitis and tooth loss with liver cancer: A systematic review - Al-Maweri, Sadeq Ali; Ibraheem, Wael Ibraheem; Al-Akhali, Mohammad Sultan; Shamala, Anas; Halboub, Esam; Alhajj, Mohammed Nasser (Elsevier, 2021)
A number of epidemiological studies have suggested a positive association between periodontal diseases and oro-digestive cancers, including liver cancer. The purpose of the present systematic review was to analyze the current evidence regarding the potential association between periodontitis and/or tooth loss and the risk of liver cancer. A comprehensive search of PubMed, Scopus and Web of Science databases was conducted in August 2019. The inclusion criteria comprised all observational studies that assessed the relationship between periodontitis or tooth loss and liver cancer. Case reports, animal studies, experimental studies, and reviews were excluded. Due to great heterogeneity among the included studies, no meta-analysis was conducted. Six studies (five prospective cohorts and one case-control) comprising 619,834 subjects (including 916 liver cancer cases) were included. The studies were conducted in the United States, Europe, and Asia. Three large-scale cohort studies reported a positive association between periodontitis or tooth loss and the risk of liver cancer. One case-control study found some association between liver cancer and loss of 12?23 teeth, but such association was not replicated in patients with greater number of tooth loss. Contrarily, two studies failed to report any association between periodontitis and/or tooth loss and the risk of liver cancer. The available evidence suggests a possible link between tooth loss/periodontitis and the risk of liver cancer. However, the evidence is not conclusive enough, a fact that drives to conduct more, well-designed, prospective cohort studies to further explore the potential association between periodontitis and the risk of liver cancer.